Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis, A Review of Pathogenesis, Clinical Features, Diagnosis and Treatment - Martyna Rozenbajgier; Justyna Wójcik-Grudzień; Paulina Pawłowska; Alicja Ozga-Stachurska (Kazimierz Wielki University, 2022)
Stevens Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, acute conditions, potentially life-threatening, immune-mediated and often unpredictable. Characteristic for SJS and TEN is acute necrosis of the epidermis and mucous membranes, caused by the extensive death of keratinocytes. These syndromes are considered hypersensitivity reactions. They are most often caused by drugs. There have also been reports of SJS / TEN being caused by infection, SJS/TEN disease is very rare and due to its rarity there is no specific pharmaceutical algorythm. Supportive care and treatment of symptoms are very important. The most crucial part of non-pharmacologic treatment of SJS/TEN is the detection and cessation of the pharmaceutical that caused the disease. The aim of this literature review was to summarize current knowledge about the pathogenesis, clinical features, diagnosis and treatment of Stevens- Johnson Syndrom and Toxic Epidermal Necrolysis. Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: Stevens-Johnson Syndrome, Toxic Epidermal Necrolysis, cutaneous adverse drug reactions